Lumican Regulates Collagen Fibril Assembly: Skin Fragility and Corneal Opacity in the Absence of Lumican - Chakravarti, Shukti (The Rockefeller University Press, 1998)
Lumican, a prototypic leucine-rich proteoglycan with keratan sulfate side chains, is a major component of the cornea, dermal, and muscle connective tissues. Mice homozygous for a null mutation in lumican display skin laxity and fragility resembling certain types of Ehlers-Danlos syndrome. In addition, the mutant mice develop bilateral corneal opacification. The underlying connective tissue defect in the homozygous mutants is deregulated growth of collagen fibrils with a significant proportion of abnormally thick collagen fibrils in the skin and cornea as indicated by transmission electron microscopy. A highly organized and regularly spaced collagen fibril matrix typical of the normal cornea is also missing in these mutant mice. This study establishes a crucial role for lumican in the regulation of collagen assembly into fibrils in various connective tissues. Most importantly, these results provide a definitive link between a necessity for lumican in the development of a highly organized collagenous matrix and corneal transparency.